2020
DOI: 10.3390/biom10020316
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Use of Antisense Oligonucleotides for Vaccine Improvement

Abstract: Antisense oligonucleotides (ASOs) are synthetically prepared short single-stranded deoxynucleotide sequences that have been validated as therapeutic agents and as a valuable tool in molecular driving biology. ASOs can block the expression of specific target genes via complementary hybridization to mRNA. Due to their high specificity and well-known mechanism of action, there has been a growing interest in using them for improving vaccine efficacy. Several studies have shown that ASOs can improve the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 144 publications
(181 reference statements)
0
20
0
Order By: Relevance
“…Several studies have shown that oligonucleotides can improve the efficacy of vaccines, either by inducing antigen modification (i.e., by enhancing expression of immunogenic molecules) or by targeting certain components of the host immune system to achieve the desired immune response. However, despite their extensive use, problems such as insufficient stability and low cellular delivery have not been sufficiently resolved to achieve effective and safe oligonucleotide-based vaccines [ 66 ]. For many years, nucleic acids and short nucleotide molecules have been used as vaccine components.…”
mentioning
confidence: 99%
“…Several studies have shown that oligonucleotides can improve the efficacy of vaccines, either by inducing antigen modification (i.e., by enhancing expression of immunogenic molecules) or by targeting certain components of the host immune system to achieve the desired immune response. However, despite their extensive use, problems such as insufficient stability and low cellular delivery have not been sufficiently resolved to achieve effective and safe oligonucleotide-based vaccines [ 66 ]. For many years, nucleic acids and short nucleotide molecules have been used as vaccine components.…”
mentioning
confidence: 99%
“…This location allowed us to estimate that its possible site of action could be at the pre-RNA level, still containing the non-coding sequences. Therefore, the probable silencing mechanism could occur through the action of an RNAse-H, which cleaves the heterodimer, or also by a steric hindrance mechanism and splicing inhibition [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the known deleterious effects of Tregs in vaccine immunogenicity and efficacy, one of the current directions of this approach is the development of subunit vaccines and molecular adjuvants targeting immune regulatory networks to improve vaccine immunogenicity [ 15 ]. The use of ASOs targeting important regulatory mechanisms is one of the most promising molecular adjuvants for vaccine improvement [ 16 ]. Several ASOs have been designed against immunomodulatory components, such as cytokines [ 29 , 30 ], immune checkpoints [ 31 , 32 ], or transcription factors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review article about the use of ASOs for vaccine improvement based on the strategy of antigen modification has recently been published [7]. The first attempts using ASOs for antigen manipulation started in 1990.…”
Section: Inhibition Of Hiv-1 Rnamentioning
confidence: 99%